Review: Myelin clearance is critical for regeneration after peripheral nerve injury - Yuan, YiMing; Wang, Yan; Wu, ShanHong; Zhao, Ming Yue (Frontiers in Neurology, 2022)
Traumatic peripheral nerve injury occurs frequently and is a major clinical and public health problem that can lead to functional impairment and permanent disability. Despite the availability of modern diagnostic procedures and advanced microsurgical techniques, active recovery after peripheral nerve repair is often unsatisfactory. Peripheral nerve regeneration involves several critical events, including the recreation of the microenvironment and remyelination. Results from previous studies suggest that the peripheral nervous system (PNS) has a greater capacity for repair than the central nervous system. Thus, it will be important to understand myelin and myelination specifically in the PNS. This review provides an update on myelin biology and myelination in the PNS and discusses the mechanisms that promote myelin clearance after injury. The roles of Schwann cells and macrophages are considered at length, together with the possibility of exogenous intervention.